Unlocking resource access for startups via the sharing economy - Kelvin W. Ivankovic (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: In recent years, the sharing economy (SE) has garnered increasing attention for its potential to enable businesses to access resources that would otherwise be difficult or costly to acquire. This is expected to be particularly beneficial for startups that face resource constraints.